2016
DOI: 10.1039/c5gc00519a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and analysis of environmentally sustainable methodologies for extraction of betulin from birch bark with a focus on industrial feasibility

Abstract: Evaluation and analysis of environmentally sustainable extraction of betulin from birch bark with a focus on large-scale industrial feasibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 22 publications
(22 reference statements)
0
21
0
Order By: Relevance
“…Together with its anti-inflammatory and wound healing effects, this makes birch bark dry extract interesting for the stabilisation of semisolid systems, such as gels and creams, acting as an active ingredient and an excipient in parallel. A common method for obtaining birch bark dry extract or particular triterpenoids is the extraction of birch bark with organic solvents [41,[44][45][46][47]. Some other production methods like Ultrasonic Assisted Extraction (UAE) [48] and sublimation [49] are described in the literature.…”
Section: Pharmacological Effects Of Triterpenoids Contained In Birch mentioning
confidence: 99%
“…Together with its anti-inflammatory and wound healing effects, this makes birch bark dry extract interesting for the stabilisation of semisolid systems, such as gels and creams, acting as an active ingredient and an excipient in parallel. A common method for obtaining birch bark dry extract or particular triterpenoids is the extraction of birch bark with organic solvents [41,[44][45][46][47]. Some other production methods like Ultrasonic Assisted Extraction (UAE) [48] and sublimation [49] are described in the literature.…”
Section: Pharmacological Effects Of Triterpenoids Contained In Birch mentioning
confidence: 99%
“…Substances isolated from natural resources may be a good choice. Betulin, a naturally abundant compound in the outer bark of birch, can be readily obtained by solvent extraction (Fridén et al 2016). Betulin represents 25-35% of the weight of the outer bark of major birch species (Krasutsky 2006), and due to its hydrocarbon skeleton, betulin possesses very low surface energy.…”
Section: Introductionmentioning
confidence: 99%
“…To date, numerous methods for the extraction of the betulin active compound from birch tree bark have been reported in the literature. State-of-the-art extraction technologies result in excellent betulin yield, i.e., ranging from 20% to 40% from the birch outer bark [7]. For instance, Rizhikovs et al reported that approximately 37% of triterpene-rich extracts were isolated from outer birch bark by hot water and Na 2 CO 3 pretreatment [8].…”
Section: Introductionmentioning
confidence: 99%